THEORETICAL AND PEDAGOGICAL FOUNDATIONS OF TEACHING METHODOLOGY FOR THE INFORMATION SECURITY DISCIPLINE IN HIGHER EDUCATION - Navruzov Bakhtiyor Ikhtiyorovich, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
This article explores the theoretical and pedagogical foundations necessary for developing an effective teaching methodology for Information Security (InfoSec) in higher education institutions. In the context of rapid digitalization and evolving cyber threats, traditional, purely technical approaches to InfoSec education are insufficient. The study argues for a holistic methodology grounded in modern pedagogical theories such as constructivism, competency-based education, and the integration of ethical and legal dimensions. Through a literature review and analysis, the article identifies key challenges—including the dynamic nature of the subject, the theory-practice gap, and varying student backgrounds—and proposes methodological solutions. These solutions emphasize active learning strategies (case studies, gamification, hands-on labs), interdisciplinary content, and continuous adaptation of curricula. The conclusion underscores that a robust pedagogical foundation is critical for cultivating not only technically proficient but also ethically responsible and adaptable information security professionals capable of addressing contemporary cyber challenges.